High-Density, Actively Multiplexed µECoG Array on Reinforced Silicone Substrate - Rachinskiy, Iakov; Wong, Liane; Chiang, Chia-Han; Wang, Charles; Trumpis, Michael; Ogren, John I.; Hu, Zhe; McLaughlin, Bryan; Viventi, Jonathan (Frontiers in Nanotechnology, 2022)
Simultaneous interrogation of electrical signals from wide areas of the brain is vital for neuroscience research and can aid in understanding the mechanisms of brain function and treatments for neurological disorders. There emerges a demand for development of devices with highly conformal interfaces that can span large cortical regions, have sufficient spatial resolution, and chronic recording capability while keeping a small implantation footprint. In this work, we have designed 61 channel and 48 channel high-density, cortical, micro-electrocorticographic electrode arrays with 400 µm pitch on an ultra-soft but durable substrate. We have also developed a custom multiplexing integrated circuit (IC), methods for packaging the IC in a water-tight liquid crystal polymer casing, and a solution for attaching the package to the electrode array. With the integrated multiplexer, the number of external wire connections can be reduced to 16 wires, thereby diminishing the invasive footprint of the device. Both the electrode array and IC were tested in-vivo in a rat model to demonstrate the ability to sense finely-localized electrophysiological signals.